AB0847 Efficacy and Safety of Canakinumab Pre-Filled Syringe in Acute Gouty Arthritis Patients with Chronic Kidney Disease Stage ≥3. (10th June 2014) - Sunkureddi, P.; Toth, E.; Brown, J.; Kivitz, A.; Stancati, A.; Richard, D.; Lheritier, K.; Möricke, R.
Abstract : Background: Chronic kidney disease (CKD) limits the treatment options in acute gouty arthritis (GA) patients due to intolerance and contraindications to available therapies. Efficacy and safety of canakinumab (CAN), a selective, fully human, anti-IL-1β monoclonal antibody, formulated as a lyophilized (CAN-LYO) powder requiring reconstitution with water vs triamcinolone acetonide (TA) in patients with acute GA was demonstrated in previous phase III trials. Objectives: To evaluate efficacy and safety of CAN liquid formulation (CAN-PFS) vs TA in a subgroup of patients with CKD stage ≥3. Methods: This was a 12-week, multicenter, double-blind, active controlled study. The design and methodology of the study have been reported earlier 1 . Here, we report results from a post-hoc analysis of the 12-week data for GA patients with CKD stage ≥3 (estimated Glomerular Filtration Rate (eGFR) <60ml/min). The primary endpoint was pain intensity in the target joint, measured on 0-100 mm VAS scale at 72 h post-dose. Secondary endpoints included time to first new attack, and safety over 12 weeks. Results: Of 388 patients, 76 had CKD stage ≥3 at baseline (CAN-PFS, n=24; CAN-LYO, n=28; TA, n=24). CAN-PFS provided a statistically significant reduction in pain intensity in the target joint vs TA from 72 h post-dose (estimated difference, -14.6mm; 95% CI:-29.0, -0.1, p≤0.05) until 7 days post-dose (-16.1mm; 95% CI: -28.4, -3.7, p=0.0115). The two CAN treatment arms were comparable. Over 12 weeks, a single dose of CAN-PFS showed a significant relative risk reduction of 90% for time to first new gout attack vs TA [HR 0.10, 95% CI (0.01, 0.78); p≤0.05]. Adverse events (AEs) were reported in 12 (50%), 11 (39.3%) and 10 (41.7%) patients in CAN-PFS, CAN-LYO and TA groups, respectively. The most frequent AEs were infections (CAN-PFS, n=3 (12.5%); CAN-LYO, n=6 (21.4%); TA, n=2 (8.3%). Serious AEs were reported in a total of 7 patients (CAN-PFS, n=2 (8.3%); CAN-LYO, n=4 (14.3%); TA, n=1 (4.2%), with infections (CAN-PFS, n=1 (4.2%); CAN-LYO, n=2 (7.1%); TA, n=0), being the most common SAEs. No deaths were reported during the study. Conclusions: This post-hoc analysis provides evidence for the efficacy of CAN-PFS compared with a potent long-acting corticosteroid in providing significant pain relief and reducing incidence of new attacks in GA patients with CKD stage ≥3 with limited treatment options. The safety profile in this sub population was consistent with that of the overall study population and with that known from previous studies. References: Sunkureddi et al. Arthirits & Rheum 2013; 65. Disclosure of Interest: P. Sunkureddi Consultant for: Novartis, Bristol Myers Squibb, Speakers bureau: Pfizer, Takeda, Bristol Myers Squibb, UCB, Amgen, Abbott, Shinogi, Savient, E. Toth: None declared, J. Brown Grant/research support: Amgen, Bristol Myers Squibb, Eli Lilly, Novartis, Merck, Pfizer, Roche, Servier, Sanofi-Aventis, Takeda, Warner Chilcott, Consultant for: Amgen, Eli Lilly, Merck, Warner Chilcott, Sanofi–Aventis, Speakers bureau: Amgen, Eli Lilly, Novartis, Merck, A. Kivitz Grant/research support: Novartis, A. Stancati Shareholder of: Novartis, Employee of: Novartis, D. Richard Shareholder of: Novartis, Employee of: Novartis, K. Lheritier Shareholder of: Novartis, Employee of: Novartis, R. Möricke: None declared DOI: 10.1136/annrheumdis-2014-eular.1850